Analisis Perilaku Pengepul kopi dalam Meningkatkan Nilai Jual Kopi pada Petani Kopi di Kecamatan Kebun Tebu Kabupaten Lampung Barat - Yusuf, Soleh; Purnamasari, Melan Susanty; Rosidah, Rosidah; Suryani, Suryani (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2025)
This study aims to analyze the behavior of coffee collectors in increasing the selling value of coffee for farmers in Kebun Tebu District, West Lampung Regency. The main issue raised is the dependence of farmers on collectors, which leads to suboptimal selling prices of coffee. The research employed a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. Informants in this study included coffee collectors, coffee farmers, and representatives of the farmers’ association. The results show that collectors have sufficient knowledge regarding coffee quality standards, market prices, and the impact of post-harvest processes on selling value. In practice, collectors play a crucial role as intermediaries between farmers and broader markets. Their strategies to increase coffee value include educating farmers, sorting, drying, and packaging coffee. However, several challenges remain, such as price fluctuations, lack of transparency in pricing, and the uneven understanding among farmers regarding coffee quality. This study recommends the development of a more transparent distribution system and ongoing training for farmers to improve coffee quality and competitiveness. Establishing a fairer relationship between collectors and farmers is essential to enhancing the welfare of coffee farmers. Keywords: collector behavior, selling value, coffee, farmers, kebun tebu district.